New Spectroelectrochemical Insights into Manganese and Rhenium Bipyridine Complexes as Catalysts for the Electrochemical Reduction of Carbon Dioxide - Barbero, Alice; Rotundo, Laura; Reviglio, Chiara; Gobetto, Roberto; Sokolova, Romana; Fiedler, Jan; Nervi, Carlo (Molecules (Basel, Switzerland), 2023)
This study aimed to demonstrate the behavior of different complexes using IR spectroelectrochemistry (SEC), a technique that combines IR spectroscopy with electrochemistry. Four different Mn and Re catalysts for electrochemical CO2 reduction were studied in dry acetonitrile. In the case of Mn(apbpy)(CO)3Br (apbpy = 4(4-aminophenyl)-2,2′-bipyridine), SEC suggested that a very slow catalytic reduction of CO2 also occurs in acetonitrile in the absence of proton donors, but at rather negative potentials. In contrast, the corresponding Re(apbpy)(CO)3Br clearly demonstrated slow catalytic conversion at the first reduction potential. Switching to saturated CO2 solutions in a mixture of acetonitrile and 5% water as a proton donor, the SEC of Mn(apbpy)(CO)3Br displayed a faster catalytic behavior.